Proteome-Wide Identification and Functional Analysis of Lysine Crotonylation in Trichophyton rubrum Conidial and Mycelial Stages - Xu, Xingye; Hu, Xiangqi; Dong, Jie; Xue, Ying; Liu, Tao; Jin, Qi (Frontiers in Genetics, 2022)
Lysine crotonylation is a newly discovered post-translational modification (PTM) with key roles in various important regulatory pathways. Despite its functional significance, there is limited knowledge about crotonylation in fungi. Trichophyton rubrum is the most common fungal pathogen in human infection and is considered a model organism of dermatophytes and human pathogenic filamentous fungi. In this study, we obtained a proteome-wide crotonylation profile of T. rubrum, leading to the identification of 14019 crotonylated sites on 3144 proteins. The crotonylated proteins were significantly involved in translation and in various metabolic and biosynthetic processes. Some proteins related to fungal pathogenicity were also found to be targets of crotonylation. In addition, extensive crotonylation was found on histones, suggesting a role in epigenetic regulation. Furthermore, about half of the crotonylated proteins were specific to either the conidial or the mycelial stage, and functional enrichment analysis showed some differences between the two stages. The results suggest that the difference in crotonylation between the two stages is not due to differences in protein abundance. Crosstalk of crotonylation with acetylation, propionylation, and succinylation suggests distinct regulatory roles. This study is the first crotonylation analysis in dermatophytes and human pathogenic filamentous fungi. These results represent a solid foundation for further research on PTM regulatory mechanisms in fungi and should facilitate improved anti-fungal strategies against these medical important species.